ANALISIS PENGARUH PERSON-ORGANIZATION FIT TERHADAP KINERJA KARYAWAN: KOMITMEN ORGANISASIONAL DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOUR SEBAGAI VARIABEL INTERVENING (STUDI PADA KARYAWAN PT TELKOM WITEL PEKALONGAN) - Maria, Helena Stefani; Yuniawan, Ahyar (Diponegoro Journal of Management, 2016)
This study  is motivated  by the  performance level of  employees at  PT Telkom Witel Pekalongan which has not optimal. Based on reseacrh gaps indicated  issues raised by person-organization fit, organizational commitment, and organizational citizenship behaviour to support the process of employee performance. This study aimed to analyze the influence of person-organization fit on organizational commitment, the influence of person-organization fit on organizational citizenship behavior, the influence of person-organization fit on employee performance, the influence of organizational commitment on employee performance, and the influence of organizational citizenship behavior on employee performance. This study uses path analysis model with two intervening variables:  organizational commitment and organizational citizenship behavior. The sample which is used in this study were 92 employees. The questionnaires were distributed by simple random sampling method and data were analyzed by using linear regression method.The results showed that the influence of person-organization fit on employee performance with organizational commitment and organizational citizenship behavior as the intervening variables amounted to 92.57% while 7.43% is explained by other factors beyond the variables used in this study. The regression results indicate that the person-organization fit influence positively and significantly on organizational commitment, organizational citizenship behavior and employee performance, and then organizational commitment and organizational citizenship behavior is also influence  positively and significantly on employee performance.